Managing recurrent rectal prolapse in women: a single-center study - Rzadkowski, Stanislaw; Ciesielski, Przemyslaw; Kolodziejczak, Malgorzata (Frontiers in Surgery, 2025)
Recurrent rectal prolapse (RRP) presents a significant clinical challenge due to the absence of standardized treatment guidelines and its impact on patients' quality of life. This retrospective study evaluates the outcomes of surgical management for RRP in a single-center cohort. We analyzed female patients (median age of 73) who underwent surgical treatment for RRP between 2014 and 2022. A total of 30 patients received either abdominal (n = 12) or perineal (n = 18) procedures, including ventral mesh rectopexy (VMR), resection rectopexy, Altemeier or Delorme techniques. Re-recurrence was more common following perineal procedures (39%) than abdominal approaches (25%). VMR and resection rectopexy demonstrated comparable success rates of 75%, while Altemeier and Delorme procedures showed 60% and 67% success, respectively. Functional outcomes improved significantly postoperatively, with the EQ-VAS quality of life score increasing from a median of 50 preoperatively to 75 at three years. Fecal incontinence and constipation scores (Wexner and CCCS) also showed marked improvement. Complications were minor and managed conservatively, with no cases of mesh erosion or anastomotic dehiscence reported. These findings support abdominal procedures, especially VMR and resection rectopexy, as the preferred treatment for medically fit patients with RRP. Perineal approaches remain viable for high-risk patients but are associated with higher recurrence. Although limited by its retrospective design, small sample size, and non-randomized treatment allocation, this study contributes valuable data to inform surgical decision-making in the management of RRP.